The role of the paraglacial environment in the transformation of glacial wartanian relief in Poland - Rdzany, Zbigniew (Bulletin of Geography. Physical Geography Series, 2015)
The article comprises a justification for the need to distinguish the record of the paraglacial environments in the belt of relief formed as a result of the Warta Glaciation in Poland. The zone covers the foreland of the Weichselian Glaciation, occupying a strip of land from several to more than 200 kilometres in width. Simplified, two periods are marked in the history of views on relief genesis of the area. The first, which covers the first half of the 20th century, was dominated by the idea of glacial genesis of the area. The latter period is characterised by the discussion between advocates of the periglacial character of relief of the Wartanian zone and those who defended the thesis of the good preservation of glacial relief of the area. Taking the paraglacial environment into account in analysing relief transformations introduces a new quality and may result in a more complete and precise evaluation of post-Wartanian morphogenesis. It is also consistent with tendencies in worldwide literature and results from the principle of uniformitarianism.